1995
DOI: 10.1085/jgp.105.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of graded potentials at the photoreceptor-interneuron synapse.

Abstract: To characterize the transfer of graded potentials and the properties of the associated noise in the photoreceptor-interneuron synapse of the blowfly (CaUiphora vicina) compound eye, we recorded voltage responses of photoreceptors (R1-6) and large monopolar cells (LMC) evoked by: (a) steps of light presented in the dark; (b) contrast steps; and (c) pseudorandomly modulated contrast stimuli at backgrounds covering 6 log intensity units. Additionally, we made recordings from photoreceptor axon terminals. Increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 51 publications
8
149
0
Order By: Relevance
“…Spatial antagonism of the first-order interneurons (LMCs) was implemented via weighted subtraction of nearest neighbors in the hexagonally sampled inputs to allow transmission of 70% static luminance and thus match the weak lateral inhibition described from LMC recordings in the same dragonfly species (Laughlin, 1974). LMC temporal filters were derived from Juusola et al (1995), implemented with a relaxed high-pass filter (lower corner frequency 8 Hz) and a small DC component (10%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial antagonism of the first-order interneurons (LMCs) was implemented via weighted subtraction of nearest neighbors in the hexagonally sampled inputs to allow transmission of 70% static luminance and thus match the weak lateral inhibition described from LMC recordings in the same dragonfly species (Laughlin, 1974). LMC temporal filters were derived from Juusola et al (1995), implemented with a relaxed high-pass filter (lower corner frequency 8 Hz) and a small DC component (10%).…”
Section: Methodsmentioning
confidence: 99%
“…Such complex temporal filtering would lead to weak outputs from even a purely multiplicative ESTMD. In addition to varying the term coefficients, we further tested two model variants ( ϭ 200 ms, ϭ 100 ms) that simulate variation in high-pass filtering that could represent differences in the state of light adaptation (Juusola et al, 1995;van Hateren and Snippe, 2001) or even a change in temperature (Tatler et al, 2000). At low contrasts (Fig.…”
Section: Evidence For An Estmd-like Mechanismmentioning
confidence: 99%
“…The oscillations were exacerbated at dim conditions (Fig. 7B), where the gain of both the photoreceptor output synapses and synaptic feedbacks is the highest (Juusola et al, 1995;Zheng et al, 2006), thereby leaving the lamina network most perturbable to intrinsic activity. Longer recordings indicated that the oscillations in mutant LMCs carried different frequencies during and after light adaptation (Fig.…”
Section: Back Bump Waveforms In Dskmentioning
confidence: 99%
“…The smallest change in presynaptic potential that can be transmitted reliably is a measure of resolution, and, at the inhibitory synapses between L-neurons, unreliability in transmission limits the number of discrete signal levels they can convey to ϳ5 at best. In contrast, in fly compound eyes recordings of responses to light stimuli from photoreceptors or second-order large monopolar cells (LMCs) (Laughlin et al, 1987;Juusola et al, 1995) indicate a performance an order of magnitude better, enabling LMCs to resolve 2% modulations in light intensity (Laughlin, 1989). In daylight, the photoreceptor to LMC synapse contributes 50 -70% of the noise in the LMC, the remainder originating in photoreceptors (Laughlin et al, 1987).…”
Section: Synaptic Performancementioning
confidence: 99%